Reduced Reward Responsiveness in Women With Moderate - to - Severe Premenstrual Syndrome: Evidence From a Probabilistic Reward Task - Hou, Lulu; Chang, Lei; Chen, Lirong; Zhou, Renlai (Frontiers in Psychiatry, 2020)
Nearly 50% of women of reproductive age worldwide experience premenstrual syndrome (PMS). Women with PMS exhibit low positive affect and low frontal electroencephalography asymmetry scores, both of which are associated with reward processing. These findings suggest that women with PMS may exhibit deficiencies in reward processing. A probabilistic reward task based on signal detection approach was used to assess reward responsiveness in 30 women with moderate-to-severe PMS and 31 controls without PMS. The results revealed that in the late luteal phase, the women with moderate-to-severe PMS exhibited lower response bias and lower hit rate toward more frequently rewarded stimuli (rich stimuli) than the controls. By contrast, the response bias and hit rate did not differ between the two groups in the follicular phase. The group differences still remained after controlling for anhedonic symptoms. Furthermore, trial-by-trial probability analyses revealed that women with moderate-to-severe PMS exhibited a trend of having a higher miss rate for rich stimuli than the controls. In particular, when a rich stimulus was preceded by an infrequently rewarded stimulus (a rewarded lean stimulus), participants in the PMS group exhibited a trend for higher miss rate than those in the control group in the late luteal and follicular phases. However, group differences in the probability analyses were nonsignificant after controlling for anhedonic symptoms. These results provide preliminary evidence that women with moderate-to-severe PMS exhibit dysfunctional reward responsiveness and impaired ability to modulate their behavior as a function of prior reinforcement.